The art of looking: four generations of Aracil photographers - Agustín, Carmen; Clavero Galofré, Manuel (Revista General de Información y Documentación, 2022)
The photographers of the Aracil family are studied, four generations dedicated to the photographic medium in Linares (Jaén), Infantes (Ciudad Real), Barcelona, Zaragoza, Madrid, San Sebastian and Tafalla (Navarra), over a century: José Aracil Pérez; his son José Aracil Tovar; his wife, Matilde López Anula and their children, León, Ángel, Pedro and Isaac Aracil López, as well as Matilde Aracil, Ángel’s daughter. The cities where they worked are located, the context in which they did it and the work preserved to this day is identified. The study is carried out by analyzing archival, newspaper and bibliographic sources such as yearbooks and national, regional and local guides. Among the results achieved, the knowledge of their biographies, the contextualization of their professional careers and the characterization of their work stand out.